Revestimento interno de tubos de aço api 5l grau b com nitreto de titânio depositado a plasma com gaiola catódica - Sousa, Israel de Macedo (Universidade Federal Rural do Semi-Árido, 2017)
API 5L Grade B tubes are the most used in the construction of pipelines and production lines for oil transportation. These pipes may have internal corrosion due to several factors, such as the reaction of components such as O2, H2S and CO2 with the metal surface. Due to the action of corrosion, pipelines and tubes fail to cause oil spills, leading to material losses and contamination of soils, lakes, rivers and aquifers. In this work we used the Cathodic Cage Plasma Nitriding technique for the inner coating of samples of API 5L grade B steel tubes with titanium nitride (TiN) films, deposited in plasma, searching for an alternative for the deposition of a uniform, corrosion-resistant film inside these tubes. The cathodic cage was installed concentrically inside the tube, manufactured in pure grade 1 commercial titanium with external diameter of 50.0 mm, 2.0 mm thick, 40.0 mm high and holes with a diameter of 8.0 mm equally spaced. The treatments were performed at 1.5 mbar, with temperatures of 400 and 450 ºC and treatment times of 3, 4 and 5 h. A gas mixture composed of 40% H2, 40% Ar and 20% N2 was used. The treated samples were characterized by X-ray Diffraction, Scanning Electron Microscopy, Microhardness and Raman Spectroscopy. Most of the samples treated presented a uniform appearance and gold color, indicating the formation of Titanium Nitride near the stoichiometric condition. The XRD and Raman Spectroscopy analyzes indicated the presence of Titanium Nitride in the δ-TiN phase. It has been found that increasing the treatment temperature for a same time provides an increase in the thickness of the deposited layer. These results indicate the efficiency of this process and show that the formation of a uniform layer composed mainly of Titanium Nitride (TiN), potentiating, according to previous studies, an increase in the resistance to corrosion
Keywords: Tecnologia de Dutos; Revestimento interno; Gaiola Catódica; Ducts Tecnology; Internal Coating; Cathodic cage; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA